Mechanical properties of cubic Cu3N and Cu4N: A theoretical investigation. (September 2021) - Li, Shina; Hao, Jingjing; Yu, Suye
Abstract: We derive the elastic and mechanical characteristics of cubic P m 3 ‾ m Cu3 N and Cu4 N via the first-principles density functional theory (DFT) calculations and elastic theory. For cubic Cu3 N and Cu4 N, the relaxed unit-cells match up with available data. The electronic density of states (DOS) confirms that Cu3 N is a semiconductor and Cu4 N is metallic. From single-crystal elastic constants, Cu3 N and Cu4 N are both mechanically stable. Polycrystalline properties are systematically predicted, including bulk moduli B, Lame's constants λ, and more. Cu3 N and Cu4 N are ductile based on Pugh criteria and Poisson's ratio. The elastic anisotropy is derived by analysis of anisotropy factors, directional elastic moduli, and Poisson's ratio σ. These demonstrate that the anisotropic degree of Cu3 N is greater than that of Cu4 N. We also predicted the velocities of sounds in different propagation directions, as well as the Debye temperature θ D . The higher θ D of Cu4 N manifests that it has larger microhardness than Cu3 N. Highlights: The mechanical properties of metallic P m 3 ‾ m Cu4 N are investigated for the first time. Cu3 N and Cu4 N are both mechanically stable and ductile in the cubic P m 3 ‾ m phase. The anisotropic degree of Cu3 N is greater than that of Cu4 N. Debye temperature, sound velocities along [100], [110] and [111] are derived.